Elite rugby players have unique morphological characteristics of the hamstrings and quadriceps femoris muscles according to their playing positions - Kawama, R.; Okudaira, M.; Shibata, S.; Shimasaki, T.; Maemura, H.; Tanigawa, S. (Journal of Human Kinetics, 2022)
Rugby is a popular sport requiring high-intensity and maximal speed actions. Numerous studies have demonstrated that physical performance variables, such as strength, sprinting, and jumping, are different between the forwards and backs. However, there is little information about muscle morphological characteristics specific for each rugby playing position. This study aimed to clarify the morphological characteristics of the thigh muscles in forwards and backs. Ultrasound images were obtained from the proximal, middle, and distal regions of the thigh. Then, the anatomical cross-sectional areas of particular muscles in the hamstrings and quadriceps femoris were calculated for seven forwards, seven backs, and ten non-athletes. The anatomical cross-sectional areas were normalised by the two-third power of lean body mass, and the normalised values of the three regions were averaged as that of the individual muscle. In the hamstrings, the normalised anatomical cross-sectional areas of the biceps femoris long head were significantly greater in forwards than in non-athletes, whereas those of the semitendinosus were significantly greater in backs than in non-athletes. Furthermore, in the quadriceps femoris, the normalised anatomical cross-sectional areas of the rectus femoris and vastus intermedius were significantly greater in forwards than in backs and non-athletes. These results suggest that forwards have great muscularity of the biceps femoris long head and vastus intermedius which can generate large force, whereas backs possess great muscularity of the semitendinosus which can generate high contraction velocity. These findings allow coaches to design more effective training programs according to particular rugby playing positions.